Additive manufacturing for thermal management applications: from experimental results to numerical modeling. (May 2021) - Favero, G.; Bonesso, M.; Rebesan, P.; Dima, R.; Pepato, A.; Mancin, S.
Abstract: Recently, Additive Manufacturing (AM) of metal components has opened new frontiers in heat transfer applications, going beyond the capabilities of conventional technologies. Despite the great design freedom offered by AM, when dealing with metals, there are a few issues that should be considered to exploit the great capabilities of this manufacturing technology. In fact, the surface roughness of the components is expected to affect the performance of the devices, which can be remarkably different from the ones simulated with computer codes. This paper presents a critical analysis of the accuracy of the numerical tools to simulate the fluid flow behaviour inside channels obtained via AM, showing the major limitations of the standard approaches to accurately predict the pressure drops in straight and complex channels. Three different copper channels of growing complexity were built via SLM (Selective Laser Melting) and then they were experimentally tested to evaluate the predictive abilities of the numerical model. The results revealed that the surface roughness deeply affects the fluid flow, thus the numerical models need to be calibrated to become reliable design tools. The proposed procedure can be considered the first attempt in this direction and allows for a proper integration of the AM with the numerical simulation tools to boost the design capabilities of SLM technology.